Microfinance and the business of poverty reduction: Critical perspectives from rural Bangladesh - Banerjee, Subhabrata Bobby; Jackson, Laurel (Human relations (New York), 2017)
In this article we provide a critical analysis of the role of market-based approaches to poverty reduction in developing countries. In particular, we analyse the role of microfinance in poverty alleviation by conducting an ethnographic study of three villages in Bangladesh. Microfinance has become an increasingly popular approach that aims to alleviate poverty by providing the poor new opportunities for entrepreneurship. It also aims to promote empowerment (especially among women) while enhancing social capital in poor communities. Our findings, however, reflect a different picture. We found microfinance led to increasing levels of indebtedness among already impoverished communities and exacerbated economic, social and environmental vulnerabilities. Our findings contribute to the emerging literature on the role of social capital in developing entrepreneurial capabilities in poor communities by highlighting processes whereby social capital can be undermined by market-based measures like microfinance.